Aloe-emodin inhibits African swine fever virus replication by promoting apoptosis via regulating NF-κB signaling pathway - Yizhuo Luo; Yunlong Yang; Wenru Wang; Qi Gao; Ting Gong; Yongzhi Feng; Dongdong Wu; Xiaoyu Zheng; Guihong Zhang; Heng Wang (Virology Journal)
Abstract African swine fever (ASF) is an acute infectious haemorrhagic fever of pigs caused by African swine fever virus (ASFV). Aloe-emodin (Ae) is an active ingredient of Chinese herbs with antiviral, anticancer, and anti-inflammatory effects. We investigated the antiviral activity and mechanism of action of Ae against ASFV using Real-time quantitative PCR (qPCR), western blotting, and indirect immunofluorescence assays. Ae significantly inhibited ASFV replication. Furthermore, transcriptomic analysis revealed that ASFV infection activated the NF-κB signaling pathway in the early stage and the apoptosis pathway in the late stage. Ae significantly downregulated the expression levels of MyD88, phosphor-NF-κB p65, and pIκB proteins as well as the mRNA levels of IL-1β and IL-8 in porcine alveolar macrophages (PAMs) infected with ASFV, thereby inhibiting the activation of the NF-κB signaling pathway induced by ASFV. Flow cytometry and western blot analysis revealed that Ae significantly increased the percentage of ASFV-induced apoptotic cells. Additionally, Ae promoted apoptosis by upregulating the expression levels of cleaved-caspase3 and Bax proteins and downregulating the expression levels of Bcl-2 proteins. This suggests that Ae promotes apoptosis by inhibiting the NF-κB pathway, resulting in inhibition of ASFV replication. These findings have further improved therapeutic reserves for the prevention and treatment of ASF.